2019
DOI: 10.1016/j.asmart.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy comparisons of intra-articular knee injection between the new modified anterolateral Approach and superolateral approach in patients with symptomatic knee osteoarthritis without effusion

Abstract: Background Intra-articular knee injection with steroid or various other agents have been used to control the local inflammation and relieve pain in the osteoarthritis knee. To achieve the maximal potential therapeutic worth and decrease the complications from the inaccurate knee injection, these medications should be delivered directly into the intra-articular space. Injection technique is one of the most important factors for accuracy of knee injection. Therefore, this study was aimed to propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The majority of Level I studies gathered in this review (8/12) 14-21 compared the accuracy of ultrasound-guided versus blind or landmark injection/arthrocentesis. Only 4 of 12 studies 22 , 23 , 24 , 25 compared the accuracy of anatomical-guided approaches. The majority of studies recruited patients with radiographically confirmed knee osteoarthritis (9/12 studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of Level I studies gathered in this review (8/12) 14-21 compared the accuracy of ultrasound-guided versus blind or landmark injection/arthrocentesis. Only 4 of 12 studies 22 , 23 , 24 , 25 compared the accuracy of anatomical-guided approaches. The majority of studies recruited patients with radiographically confirmed knee osteoarthritis (9/12 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Cunnington et al 21 used an inexperienced rheumatology trainee for all ultrasound-guided injections and still had relatively high accuracy rates, 91% (32/35), compared with clinical examinationeguided IAKI performed by rheumatology consultants (median 15 years' experience), 82% (27/33). Interestingly in the anatomical accuracy comparison chart in Table 5, Chernchujit et al 24 reported that the accuracy for blind IAKI to superolateral approach only was 58% (38/66).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in 90 o -bended knee position, a study using squishing technique [12] and post-injection mini airarthrography [13] showed higher accuracy (89%) of modi ed anterolateral approach compared to superolateral approach (58%) [14].…”
Section: Introductionmentioning
confidence: 95%